1998
DOI: 10.1038/nm0598-601
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a recombinant plant monoclonal secretory antibody and preventive immunotherapy in humans

Abstract: A functional comparison was made between a monoclonal secretory antibody generated in transgenic plants and its parent murine IgG antibody.The affinity constants of both antibodies for a Streptococcus mutans adhesion protein were similar. However the secretory antibody had a higher functional affinity due to its dimeric structure. In the human oral cavity, the secretory antibody survived for up to three days, compared with one day for the IgG antibody. The plant secretory antibody afforded specific protection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
248
3
6

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 451 publications
(259 citation statements)
references
References 18 publications
2
248
3
6
Order By: Relevance
“…Passive immunization with antibodies from several different species has been used as immunotherapy against dental caries (25,26) and periodontitis (27)(28)(29)(30)(31)(32). Previous studies have shown that antibodies are actively transported to the egg yolk of immunized hens (33).…”
Section: Discussionmentioning
confidence: 99%
“…Passive immunization with antibodies from several different species has been used as immunotherapy against dental caries (25,26) and periodontitis (27)(28)(29)(30)(31)(32). Previous studies have shown that antibodies are actively transported to the egg yolk of immunized hens (33).…”
Section: Discussionmentioning
confidence: 99%
“…Only one of these has been tested in humans: a chimeric secretory IgG-IgA antibody against a surface antigen of Streptococcus mutans, the primary causal agent of tooth decay. This tobacco-produced antibody was applied topically to teeth and found to be as effective as an IgG produced in a murine hybridoma at preventing recolonization by S. mutans 8 . The second antibody, a humanized anti-herpes-simplex virus (HSV) antibody made in soybean, was effective in the prevention of vaginal HSV-2 transmission in a mouse model 3 .…”
Section: Antibody Production In Plantsmentioning
confidence: 99%
“…For mucosal applications, this is not likely to present problems for most people because plant glycoproteins are ubiquitous in the human diet. There has been no evidence of allergic reaction or of a human anti-mouse antibody (HAMA) response in 60 patients receiving topical oral application of a secretory IgA specific to S. mutans 8 .…”
Section: Antibody Production In Plantsmentioning
confidence: 99%
“…The secretory version of this antibody accumulated at high levels in the plant, retained specificity against Streptococcus mutans, and conferred protection against dental caries [35]. In fact, a milestone for plant molecular farming was the first EU approval for the commercialization of a plant-made recombinant product, which was awarded to California based company Planet-Biotech for the production of sIgG/A as a medical device for human health.…”
Section: Deleted: Itsmentioning
confidence: 99%
“…Deleted: [20,34] Deleted: [35] Deleted: SIgA In their natural biofactories, the lymphocytes, antibodies are synthesized through the cell endomembrane system. Antibody synthesis requires coordinated expression, folding and assembly of H and L chains.…”
Section: Deleted: Alsomentioning
confidence: 99%